INOVASI DALAM PEMBELAJARAN MATEMATIKA UNTUK MEMBEKALI MAHASISWA MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Isna Wardiah; Nurmahaludin Nurmahaludin (Politeknik Negeri Jakarta, 2019)
AbstractIndonesia is facing an era of industri 4.0 that causes disruption in the labor market. Higher education institutions are obliged to equip students with life skills through lecturing process. It needs innovation for mathematics learning to give hard skills and soft skills for the students. Learning method that will be tested is Student team achievement division (STAD). The objective of this research is to equip students to face the era of industri 4 by improving soft skill and hard skill through STAD method. This is a classroom action research with students of IT study program of Poliban that learning mathematics II as the object. The study was conducted in two cycles. The dependent variables are Student's Soft skills (communication, discipline, teamwork, and creativity) and Students’ hard skills (test scores). The independent variable is the STAD. Soft skills data were analyzed by calculating the mean of the softskill indicator and the hardskill data by measuring the mean of the test score. In the end, STAD cooperative learning improves students' soft skills, it can be seen from the observation value of each indicator which reaches ≥ 2.4 with the criteria of